Spectrophotometric Determination of Pantoprazole by Precipitation Reactions and by HPLC - Raju, M.S.M.; Sankar, D.G.; Sastry, C.S.P. (Asian Journal of Chemistry, 2016)
Three simple and sensitive spectrophotometric methods (methods A, B and C) based on precipitation reactions and one HPLC method (method D) have been described for the estimation of pantoprazole (PTP) in pure form and its formulations. PTP forms insoluble molecular complexes with alkaloid precipitants like phosphomolybdic acid (PMA, method A), ammonium molybdate (AM, method B) or with iodine (I2, method C) under acidic conditions. In addition, colour reactions have been combined to estimate each precipitant (and in turn PTP) either released from the complex (with PMA or AM) or the unreacted precipitant in the filtrate (I2). They are based on the colour formation with cobalt nitrate – ethylene diamine tetraacetic acid disodium salt complex [Co(II)-EDTA, λmax, 750 nm for PMA, method A], potassium thiocyanate (SCN–, λmax 450 nm for AM, method B) or p-N-methyl amino phenol sulphate-sulfanific acid (PMAP-SA, λmax 525 nm for I2, method C). Method D is an HPLC method in which silica column with a mobile phase consisting of acetonitrile, methanol and water (30 : 30 : 40) and beclomethasone dipropionate as an internal standard were utilised. The eluents were monitored at a detection wavelength of 289 nm. The results obtained are reproducible and are statistically validated.